Edukasi Masyarakat Dalam Pengembangan Desa Wisata Berbasis Community Based Tourism (CBT) Di Desa Semboro Kabupaten Jember - Alissa Ernawati Adisiswanto; Noor Faridha (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Tourism management is an effort to realize a tourist village that has great natural potential. Community service activities carried out in Semboro Village, Jember Regency aim to provide benefits for Pokdarwis and the community who play a direct role in its development. Although orange production in Jember Regency has increased, farmers do not feel the same benefits because the price of oranges is uncertain. Therefore, orange farmers, especially in Semboro District, are eager to develop existing orange plantation businesses into tourism businesses. If we look at the market potential based on tourist visits to Jember Regency, the growth of agrotourism businesses in the area looks very promising. This community service activity is carried out by providing education through lectures and questions and answers. The results of this activity are very useful for increasing community knowledge and abilities. The results of the evaluation of the activity process show that the community understands how to realize a tourist hamlet in Semboro Hamlet, Jember Regency.